A Deep AI Analytics for Targeted Academic Intervention and Engagement Profiling - Sathishkumar, Thangiah; Raghavendra Gupta, T.; Hemanth, S. V.; Roy, Dharmendra Kumar (Journal of Engineering Education Transformations, 2026)
Indeed, in the rapidly developing field of education, though environments enabling AI-mediated learning are becoming more and more popular, the problem of the feasibility of real-time behavior modeling and forecasting academic achievement analytics remains acute and demands explanatory and adaptive solutions. Conventional learning analytics models tend to fall short of incorporating multi-modal information and do not provide active intervention systems. To overcome such a shortfall, BEACON (Behavioral Engagement-Academic Classifier Optimizer Network) is proposed in this study, which is an original Artificial Intelligence (AI) approach that combines deep sequential learning and explainable graph analytics, utilizing them to model student behavior and predict academic performance on the fly. BEACON has four major sub-processes. They include Multi-modal Data Ingestion Layer, which collects time-series Learning Management System (LMS) logs, facial affective inputs, and engagement data via IoT sensing devices, Behavioral Pattern Graph Construction, where the details are converted to dynamic graphs with Temporal Graph Neural Networks (TGNN), Academic Success Prediction Engine, based on a hybrid Long Short-Term Memory (LSTM)-Transformer sequence model, which predicts course-specific outcomes, and Explainable Intervention Recommender, which uses SHapley Additive exPlanations (SHAP) values to identify student-specific interventions. The evaluation of BEACON was already being carried out using standard real-time dataset and had a perfect 92.4% success finding struggling students in week four of the semester and enhanced positive student results by 18.7%, with student satisfaction on AI-delivered feedback interventions achieving the highest (24.2%) difference. Besides making learning analytics go beyond the traditional dashboard level, this framework supports ethical AI to be accompanied by transparency in a way that makes education sustainable and personalized.